Pulmonary outflow obstruction protects against heart failure in adults with congenitally corrected transposition of the great arteries. (1st October 2015) - Helsen, Frederik; De Meester, Pieter; Van Keer, Jan; Gabriels, Charlien; Van De Bruaene, Alexander; Herijgers, Paul; Rega, Filip; Meyns, Bart; Gewillig, Marc; Troost, Els; Budts, Werner
Abstract: Background: Pulmonary outflow tract obstruction (POTO) reduces systemic atrioventricular valve (SAVV) regurgitation severity in congenitally corrected transposition of the great arteries (ccTGA). Therefore, pulmonary artery banding is proposed as a palliative intervention. We aimed to investigate the effect of native or surgically induced POTO on event-free survival, defined as the composite of all-cause mortality, heart transplantation, or congestive heart failure (CHF). Methods and results: Patients with ccTGA (n = 62; median age 27.5 (IQR 18.4–39.4) years; 39% with POTO) were selected from the Adult Congenital Heart Disease database of a tertiary hospital. At first visit, SAVV regurgitation ≥ 3/4, systemic RV dysfunction ≥ moderate, and CHF were present in 26%, 26%, and 15% of patients, respectively. Over a mean follow-up time of 10.1 ± 6.1 years, all-cause mortality, rate of heart transplantation, and CHF were 18%, 8% and 40%, respectively. SAVV regurgitation (HR: 1.99; 95% CI: 1.01–3.92; P  = 0.048) and systemic RV dysfunction severity (HR: 1.89; 95% CI: 1.05–3.37; P  = 0.033) were associated with the composite endpoint, independently of age at baseline, POTO, Ebstein-like malformation, and systemic RV dilatation. Patients with POTO had lower risk for developing SAVV regurgitation ≥ 3/4 (HR: 0.18; 95% CI: 0.05–0.58; P  = 0.004) and moderate systemic RV dysfunction (HR: 0.34; 95% CI: 0.15–0.78; P  = 0.011). When POTO was present, the mean progression-free interval for the composite endpoint increased from 11.2 to 18.1 years ( P  = 0.035). Conclusions: POTO is associated with an improved event-free survival in adults with ccTGA.